2011
DOI: 10.1128/aac.00560-11
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Salmonella enterica Serovar Typhimurium Isolates Harboring a Chromosomally Encoded CMY-2 β-Lactamase Gene Located on a Multidrug Resistance Genomic Island

Abstract: Since 2004, extended-spectrum cephalosporin (ESC)-resistant Salmonella enterica serovar Typhimurium (S. Typhimurium) isolates have been detected from cattle in the northern major island of Japan, Hokkaido. Resistance to ESCs was found to be mediated by CMY-2 type β-lactamase among 22 epidemiologically unrelated isolates showing indistinguishable pulsed-field gel electrophoresis patterns. Southern blot analysis using I-CeuI-digested genomic DNA demonstrated that the CMY-2 β-lactamase gene (bla(CMY-2)) was integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 31 publications
1
40
0
Order By: Relevance
“…A case in point was highlighted by a study by Shahada et al, which identified a unique 125-kb genomic island among isolates of a dominant clone of S. Typhimurium from cattle in Japan. This island, named GI-VII-6, displayed striking similarities to portions of IncA/C plasmids containing three copies of bla CMY-2 (144).…”
Section: Role Of Plasmids In Salmonella Genome Evolutionmentioning
confidence: 99%
“…A case in point was highlighted by a study by Shahada et al, which identified a unique 125-kb genomic island among isolates of a dominant clone of S. Typhimurium from cattle in Japan. This island, named GI-VII-6, displayed striking similarities to portions of IncA/C plasmids containing three copies of bla CMY-2 (144).…”
Section: Role Of Plasmids In Salmonella Genome Evolutionmentioning
confidence: 99%
“…Aminoglycoside and trimethoprim resistance genes were also identified (Table 1). A plasmid carrying the bla CMY-2 gene was detected by S1 nuclease-PFGE and Southern blot analysis (12), indicating that it appears to have been an independent acquisition by two different serovars (Fig. 2).…”
mentioning
confidence: 99%
“…To obtain the draft genome sequence, pulsed-field gel electrophoresis (PFGE) and next-generation sequencing (NGS) were performed. Briefly, plasmid DNA was purified from S1 nuclease-digested genomic DNA that had been separated by PFGE, as previously described (15), and the bands were visualized with SYBR Safe gel stain (Life Technologies Japan, Tokyo, Japan) under a blue-light transilluminator, followed by purification using a ZR-96 Zymoclean gel DNA recovery kit (Zymo Research, Irvine, CA, USA). A DNA sequencing library (insert size, 750 to 1,000 bp) was prepared using a Nextera XT DNA sample preparation kit (Illumina, Inc., San Diego, CA) for sequencing on an Illumina MiSeq sequencer (Illumina) according to the manufacturer's instructions.…”
mentioning
confidence: 99%